HUBUNGAN TINGKAT PENGETAHUAN DAN PERSEPSI ORANGTUA TERHADAP KELENGKAPAN IMUNISASI DASAR ANAK DIERA COVID-19 DI WILAYAH PUSKESMAS KEMIRI KAB.TANGERANG 2021 - Elsa Febrianti Putri; Rini Sartika (Nusantara Hasana Journal, 2022)
During the current covid-19 pandemic, an immunization service is one of the basic health services that must be implemented as a priority. Based on the results obtained from GAVI, WHO and UNICEF, many children do not receive immunizations due to disruption of routine immunization services during the Covid-19 pandemic. It must be at risk of extraordinary events (KLBI). PD3I immunization is the most effective and efficient public health effort to prevent dangerous diseases. With the Covid-19 outbreak, the community, especially mothers with children, do not come to health services to carry out complete basic immunizations, there can be morbidity and mortality due to tuberculosis, poliometry, hepatitis, diphtheria and measles. Objective to analyze and identify the relationship between parental knowledge and perceptions of optimizing children's immunizations in the Covid-19 era. This study uses quantitative, with a descriptive correlation type design. Samples were taken throughtechnique purposive sampling. The number of samples taken were 80 respondents of parents who have children aged 9-12 months with aapproach cross sectional. From the results of bivariate analysis using the chi square test ,thevalue of p-0.00 (<0.05) was obtained, so it can be concluded that there is a relationship between the level of knowledge and parental perception of the optimization of immunization for children in the Covid-19 era in the Kemiri Health Center area. The results from respondents that parents who have a good level of knowledge are 43 (71.7%) respondents and parents who have a positive perception of optimizing child immunization in the Covid-19 era are 38 respondents (77.6%).